2021
DOI: 10.3390/ijms222413222
|View full text |Cite
|
Sign up to set email alerts
|

Novel Strategy of Proxalutamide for the Treatment of Prostate Cancer through Coordinated Blockade of Lipogenesis and Androgen Receptor Axis

Abstract: Objective: Prostate cancer (PCa) is the most common malignant tumor diagnosed in men in developed countries. In developing countries, the PCa morbidity and mortality rates are also increasing rapidly. Since androgen receptor (AR) is a key driver and plays a critical role in the regulation of PCa development, AR-targeted agents provide a key component of current therapy regimens. However, even new-generation AR antagonists are prone to drug resistance, and there is currently no effective strategy for overcoming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…A newly developed AR antagonist, proxalutamide, significantly inhibits proliferation and migration, induces the caspase-dependent apoptosis, and diminishes the level of lipid droplets in PCa cells by regulating the levels of ACL, ACC, FASN, and SREBP-1. Moreover, proxalutamide can decrease AR expression in PCa cells, which may overcome the resistance of AR-targeted therapy ( 147 ). Leelamine, a pyruvate dehydrogenase kinase inhibitor, can downregulate the expressions of SREBP-1 and key fatty acid synthesis enzymes (ACLY, ACC1, FASN) at the mRNA and protein levels to suppress fatty acid synthesis against PCa progression ( 148 ).…”
Section: Targeting the Srebp-1 Signaling Pathway For Cancer Therapymentioning
confidence: 99%
“…A newly developed AR antagonist, proxalutamide, significantly inhibits proliferation and migration, induces the caspase-dependent apoptosis, and diminishes the level of lipid droplets in PCa cells by regulating the levels of ACL, ACC, FASN, and SREBP-1. Moreover, proxalutamide can decrease AR expression in PCa cells, which may overcome the resistance of AR-targeted therapy ( 147 ). Leelamine, a pyruvate dehydrogenase kinase inhibitor, can downregulate the expressions of SREBP-1 and key fatty acid synthesis enzymes (ACLY, ACC1, FASN) at the mRNA and protein levels to suppress fatty acid synthesis against PCa progression ( 148 ).…”
Section: Targeting the Srebp-1 Signaling Pathway For Cancer Therapymentioning
confidence: 99%
“…Phase II clinical trial (clinical trial information: NCT03899467) for mCRPC patients in the United States is expected to be complete by the end of 2022. It is revealed that GT-0918 as an orally available novel candidate drug acts not only by antagonizing AR but also by downregulating the lipogenesis through inhibiting the expression of ATP citrate lyase (ACL), acetyl CoA carboxylase (ACC), fatty acid synthase (FASN), and sterol regulatory element-binding protein-1 (SREBP-1). , The coinhibition of AR signaling pathway and lipogenesis process confers GT-0918 more promising prospectus to overcome drug resistance and benefit patients’ survival. TRC-253, known as JNJ-63576253, is a novel, orally available novel candidate drug that has completed phase II/A clinical trial in Nov, 2020 .…”
Section: Resultsmentioning
confidence: 99%
“…At the moment of this study, there are some novel AR antagonist candidates that have already proceeded to phase I/II clinical trials. Proxalutamide, also known as GT-0918, which shares the same scaffold with second-generation antagonists, has passed phase I clinical trial (clinical trial information: NCT02826772) with a 3-fold more potent binding affinity than enzalutamide and satisfactory tolerance . Phase II clinical trial (clinical trial information: NCT03899467) for mCRPC patients in the United States is expected to be complete by the end of 2022.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence suggests that lipid metabolism is involved in psychologic depression or chronic stress through glucocorticoid pathway and inflammatory pathway ( Zhou et al, 2019 ; Xie et al, 2020 ; Borsini et al, 2021 ). Disordered lipid metabolism is a notable feature of PCa that is driven by androgen receptor (AR) signaling ( Zadra et al, 2019 ; Gu et al, 2021 ; Zhou et al, 2021 ). In clinical PCa, lipidomic analysis revealed higher proportions of monounsaturated phosphatidylinositol (PI) and phosphatidylserine (PS) in tumors.…”
Section: Introductionmentioning
confidence: 99%